2005
DOI: 10.1093/jn/135.12.2884
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Inhibits the Activities of Cyclin-Dependent Kinases Leading to Cell Cycle Arrest in HT-29 Human Colon Cancer Cells

Abstract: Fisetin, a natural flavonol present in edible vegetables, fruits, and wine, was reported to exert anticarcinogenic effects. The objective of the current study was to examine the effect of fisetin on the cell cycle progression of the human colon cancer cell line HT-29. HT-29 cells were cultured in serum-free medium with 0, 20, 40, or 60 micromol/L fisetin. Fisetin dose dependently inhibited both cell growth and DNA synthesis (P < 0.05), with a 79 +/- 1% decrease in cell number observed 72 h after the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 44 publications
3
86
0
1
Order By: Relevance
“…Recent research have reported anti-proliferative (Chen et al, 2002;Haddad et al, 2006) and anti-metastasic effects (Chou et al, 2013) of fisetin, a polyphenolic flavonoid present in many fruits such as strawberries and cucumbers (Kim et al, 2012). Mechanisms through which fisetin exerts its action is yet to be elucidated completely, although it has been demonstrated to increase expressions of p53, down-regulate cyclin D1 and cyclin E levels (Chen et al, 2002;Lee et al, 2002;Lu et al, 2005b;Haddad et al, 2006). Present study investigates whether fisetin induces apoptosis of human osteosarcoma cells and modulats the MAPK and PI3/Akt signalling pathways.…”
Section: Introductionmentioning
confidence: 89%
“…Recent research have reported anti-proliferative (Chen et al, 2002;Haddad et al, 2006) and anti-metastasic effects (Chou et al, 2013) of fisetin, a polyphenolic flavonoid present in many fruits such as strawberries and cucumbers (Kim et al, 2012). Mechanisms through which fisetin exerts its action is yet to be elucidated completely, although it has been demonstrated to increase expressions of p53, down-regulate cyclin D1 and cyclin E levels (Chen et al, 2002;Lee et al, 2002;Lu et al, 2005b;Haddad et al, 2006). Present study investigates whether fisetin induces apoptosis of human osteosarcoma cells and modulats the MAPK and PI3/Akt signalling pathways.…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies demonstrated that fisetin and hesperetin inhibited the proliferation of cancer cells by inducing G2/M or G0/G1 arrest. For instance, fisetin induced G2/M arrest in human epidermoid carcinoma A431 cells [25], HT-29 colon cancer cells [8], and PC3 prostate cancer cells [26]. Human cervical SiHa cells treated with hesperetin displayed G2/M arrest in a dose-dependent manner as well [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that fisetin has been shown to induce apoptosis in a variety of cell lines, fisetin-mediated antiproliferative and apoptotic effects were specific for cancer cells based on differential modulation of cellular signaling pathways. The mechanisms behind fisetin's actions include induction of cell cycle arrest by altering cell cycle regulators [8], inhibition of signaling pathways such as NF-ÎșB and PI3K/Akt pathways [9,10], prevention of cell invasion and metastasis [11], and modulation of apoptotic and anti-apoptotic molecules [12]. These effects of fisetin have been evaluated on various cancer types such as colon, prostate, pancreas, and lung cancers; however, there is no study investigating the underlying mechanism(s) of fisetin in APL.…”
Section: Introductionmentioning
confidence: 99%
“…Agullo et al 29 stated that the antiproliferative effects of compounds on cancer cells are mainly due to their antioxidant potential which strengthens the findings of the present study. The extensive studies have been conducted to show that fisetin could inhibit several molecular targets, including cyclin-dependent kinases, [30][31][32] DNA topoisomerases I and II, 33,34 urokinase, 35 actin polymerization 36 and androgen receptor signaling. 37 Moreover, fisetin has been recently reported to possess interesting anticancer activity in mice lung carcinoma 38 and prostate tumours.…”
Section: Antiproliferative Activity Of Fisetinmentioning
confidence: 99%